Clinical accuracy of point-of-care urine culture in general practice - Anne Holm; Gloria Cordoba; Tina Møller Sørensen; Lisbeth Rem Jessen; Niels Frimodt-Møller; Volkert Siersma; Lars Bjerrum (Taylor & Francis Group, 2017)
Objective: To assess the clinical accuracy (sensitivity (SEN), specificity (SPE), positive predictive value and negative predictive value) of two point-of-care (POC) urine culture tests for the identification of urinary tract infection (UTI) in general practice. Design: Prospective diagnostic accuracy study comparing two index tests (Flexicult™ SSI-Urinary Kit or ID Flexicult™) with a reference standard (urine culture performed in the microbiological department). Setting: General practice in the Copenhagen area patients. Adult female patients consulting their general practitioner with suspected uncomplicated, symptomatic UTI. Main outcome measures: (1) Overall accuracy of POC urine culture in general practice. (2) Individual accuracy of each of the two POC tests in this study. (3) Accuracy of POC urine culture in general practice with enterococci excluded, since enterococci are known to multiply in boric acid used for transportation for the reference standard. (4) Accuracy based on expert reading of photographs of POC urine cultures performed in general practice. Standard culture performed in the microbiological department was used as reference standard for all four measures. Results: Twenty general practices recruited 341 patients with suspected uncomplicated UTI. The overall agreement between index test and reference was 0.76 (CI: 0.71-0.80), SEN 0.88 (CI: 0.83-0.92) and SPE 0.55 (CI: 0.46-0.64). The two POC tests produced similar results individually. Overall agreement with enterococci excluded was 0.82 (0.77-0.86) and agreement between expert readings of photographs and reference results was 0.81 (CI: 0.76-0.85). Conclusions: POC culture used in general practice has high SEN but low SPE. Low SPE could be due to both misinterpretation in general practice and an imperfect reference standard. Registration number: ClinicalTrials.gov NCT02323087.